Association between gut microbiota and pan-dermatological diseases: a bidirectional Mendelian randomization research - Wang, Yingwei; Yao, Tao; Lin, Yunlu; Ge, Hongping; Huang, Bixin; Gao, Yu; Wu, Jianming (Frontiers in Cellular and Infection Microbiology, 2024)
The gut microbiota has been tied to dermatological problems in earlier observational studies. However, it is undetermined if the gut microbiota has a causal function in dermatological diseases.Thirteen dermatological diseases were the subject of bidirectional Mendelian randomization (MR) research aimed at potential causal links between gut microbiota and those diseases. Summary statistics for the Genome-Wide Association Study (GWAS) of the gut microbiota and dermatological diseases were obtained from public datasets. With the goal of evaluating the causal estimates, five acknowledged MR approaches were utilized, along with multiple testing corrections, with inverse variance weighted (IVW) regression serving as the main methodology. Regarding the taxa that proved to be causally linked with dermatological diseases in the forward MR analysis, reverse MR was carried out. A series of sensitivity analysis were conducted to test the robustness of the causal estimates.The combined results of the five MR methods and sensitivity analysis showed 94 suggestive and 5 significant causal relationships. In particular, genus Eubacterium_fissicatena_group increased the risk of developing psoriasis vulgaris (Odds ratio [OR]=1.32, pFDR=4.36 x 10 -3 )；family Bacteroidaceae (OR=2.25, pFDR=4.39 x 10 -3 )， genus Allisonella (OR=1.42, pFDR=1.29 x 10 -2 ) and genus Bacteroides (OR=2.25, pFDR=1.29 x 10 - 2 )increased the risk of developing acne；Besides，genus Intestinibacter increases the risk of urticaria (OR=1.30, pFDR=9.13 x 10 -3 ). Reverse MR study revealed insufficient evidence of a significant causal relationship. Additionally, there was no discernible horizontal pleiotropy or heterogeneity.This study may furnish novel insights into the causality of the gut microbiota on dermatological diseases and therapeutic or preventive paradigms for cutaneous conditions.